A silicon carbide high gain differential amplifier for extreme temperature applications. (December 2022) - Yang, Jie; Zhu, Junxian
Abstract: In this paper, a high temperature, high gain differential amplifier based on a custom-built silicon carbide (SiC) N-channel junction field effect transistor (JFET) only, without using complementary P-channel devices is proposed. The operation principle of this active load differential amplifier is discussed, and the expression of the differential gain is derived. A prototype circuit is fabricated using thick film process on an alumina substrate and tested from room temperature up to 500 °C to demonstrate the high temperature capability of the proposed differential amplifier. The differential gain of 50.8 dB is achieved with 58.6 dB common-mode rejection ratio (CMRR) and 9.1 MHz gain bandwidth product (GBW) at 500 °C. Excellent linearity and low output impedance of the proposed differential amplifier are also demonstrated at various temperatures. The proposed SiC JFET high gain differential amplifier can serve as a fundamental building block of the signal conditioning circuitry to be integrated with the sensing element for extreme environment applications.